PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK BERBANTUAN BUKU AJAR APRESIASI PUISI LAMA, BARU, DAN KONTEMPORER BERBASIS NILAI BELA NEGARA DALAM MATERI MENULIS PUISI - Nurul Setyorini; Kadaryati Kadaryati; Khabib Sholeh; Joko Purwanto (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2022)
Abstract: In general, the purpose of this study is to describe the application of a project-based learning model with the assistance of the textbook "Appreciating Old, New, and Contemporary Poetry based on National Values" in improving students' poetry writing skills. The research conducted falls under the category of classroom action research. The research subjects were third-semester students majoring in Indonesian Language and Literature Education at the Faculty of Education and Teacher Training, Muhammadiyah University of Purworejo. The results of the study indicate that: 1. the implementation of the project-based learning model with the assistance of the textbook "Appreciating Old, New, and Contemporary Poetry based on National Values" can be observed through six assessment criteria according to Nurgiyantoro, including theme, meaning, imagination, language style, imagery, and diction, 2. students' ability to write poetry improved after the implementation. The project-based learning model with the assistance of the textbook "Appreciating Old, New, and Contemporary Poetry based on National Values" proved effective.Keywords: Project-Based Learning Model, "Appreciating Old, New, and Contemporary Poetry based on National Values" textbook, Poetry Writing